Young-onset hypertension in Malaysia: A mixed-methods study / Khoo Yi Yi - Khoo, Yi Yi (2020)
The continuous cumulative presence of raised blood pressure (BP) when young is a strong predictor of future cardiovascular risk. This study, which was conducted between June 2018 and December 2019, aimed to elucidate the epidemiology of young-onset hypertension (YOH) in Malaysia during the period 2006–2015, and to explore the underlying experiences and perspectives of young adults living with hypertension. Phase I involved a systematic review to identify variables for the secondary data analysis. In Phase II, data on respondents aged 18–39 diagnosed with YOH according to the 7th Joint National Committee Report (United States) were extracted from three National Health and Morbidity Surveys (2006, 2011, and 2015). Univariate analysis was used to examine associations between YOH and baseline characteristics; Chi-square test for categorical variables and analysis of variance for continuous variables. All potential confounding factors were adjusted for using multiple logistic regression analyses. In Phase III, an interpretive phenomenological approach was adopted to conduct in-depth interviews among hypertensive young adults recruited from the Department of Primary Care Medicine, University of Malaya Medical Centre. Interviews were conducted until saturation point, transcribed verbatim, followed by content analysis and thematic coding. In Phase I, twenty studies showed considerable variability in YOH epidemiology and trends worldwide. Phase II analysis revealed that the prevalence of YOH in Malaysia remained stable during 2006–2015: 17.7%, 95% CI [17.0, 18.3] in 2006, 17.0%, 95% CI [16.0, 17.9] in 2011, and 18.4%, 95% CI [17.4, 19.4] in 2015. Awareness, treatment, and control rates were suboptimal: 15% were aware of their diagnosis, of which less than 50% were on treatment and less than 40% of those on treatment had their BP controlled. iv Significant positive associations were found with sociodemographic (male, increasing age, primary education, lower income group, positive family history) and cardiovascular risk factors. The Phase III analysis revealed that young Malaysian adults were concerned about self-stigma associated with YOH and displayed a lack of insight regarding the factors involved in developing YOH. Moreover, there was cognitive dissonance between knowledge and practice. Barriers to treatment adherence were attributed to personal (time), treatment (side effects), and disease (being asymptomatic) factors. Facilitators included social support, high self-efficacy, perceived threat and severity of disease, experiencing symptomatic relief, and role-modelling. Unmet needs included shared decision-making with healthcare professionals, having long-term expectations of treatment addressed, and the usage of social media and hypertension education materials to intensify awareness of YOH among peers. The results of this study narrow the knowledge gap on YOH epidemiology in Malaysia by providing crucial information on the pervasiveness of hypertension among young adults. They also indicate that an understanding of young adults’ lived illness experiences is critical to improving treatment adherence and BP control. Additionally, they highlight the need to treat young adulthood as a separate entity in research planning, programming, and policymaking. Thus, this study provides a basis upon which health policymakers and relevant stakeholders can build non-communicable disease policies and health promotion strategies specially targeted at young adults who are in the prime of life. Keywords: Cardiovascular disease, epidemiology, Malaysia, young-onset hypertension, young adults